Culinary skills of elderly practitioners of aquatic physical activities (Research, Society and Development, 2020)
The practice of culinary skills significantly assists in promoting and maintaining healthy eating habits. In the elderly population, the practice of culinary skills may be related to the autonomy of these individuals, as well as contributing to active behaviors in daily life. The aim of the study was to evaluate the culinary skills of elderly people who practice aquatic physical activities. Descriptive research and quantitative approach, which evaluated the elderly in four gyms that offered aquatic activities in Curitiba city, Paraná State. Data were collected through an interview or by completing a questionnaire, with questions about socioeconomic data, health status, physical activity practice and cooking skills. Thirty elderly people participated in the research, most of them female (90%), with income of more than 10 minimum wages (30%), with higher education (60%) and married (50%). Regarding the culinary skills questionnaire, it was found that the elderly had good availability of fruits and vegetables at home (score 0.91 ± 0.12), as well as confidence to prepare meals using fruits, vegetables and condiments (score 3.98 ± 0.55). In addition, 50% of participants prepare meals with basic ingredients daily. In general, the elderly demonstrated to know the culinary terms and techniques presented in the questionnaire, except for the term “Blanch” which was not well known and the technique for measuring liquids. We concluded, therefore, that the elderly have positive culinary skills and eating practices, as well as confidence in the practice of cooking.